SAE Technical Paper Series 1999
DOI: 10.4271/1999-01-3338
|View full text |Cite
|
Sign up to set email alerts
|

Best Available Technology for Emission Reduction of Small 4S-SI-Engines

Abstract: Small off-road 4-stroke SI-engines have extraordinarily high pollutant emissions. These must be curtailed to comply with the new Swiss clean air act LRV 98. The Swiss environmental protection agency (BUWAL) investigated the state of the technology. The aim was a cleaner agricultural walk behind mower with a 1 OkW 4-stroke SI-engine. Two engine designs were compared: side-valve and OHV. A commercially available 3-way catalytic converter system substantially curtailed emissions: In the ISO 8178 G test-cycle-aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…On the other hand, the mean emissions of HC + NO x are equal to 2.4 ± 0.2 g/kWh, which means that they are lower than the permissible limits by 70%. The research is consistent with the results of other scientists who studied the engines of mobile non-road machines in real working conditions; e.g., Mayer et al, in 1999, showed CO emissions at a level of 180 g/kWh and HC + NO x at a level of 12.6 g/kWh [28]. Mitianiec and Rodak, in 2012, tested a 4.5 kW (two-stroke) engine, showing CO 2 emissions at a similar level of 100 g/kWh.…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, the mean emissions of HC + NO x are equal to 2.4 ± 0.2 g/kWh, which means that they are lower than the permissible limits by 70%. The research is consistent with the results of other scientists who studied the engines of mobile non-road machines in real working conditions; e.g., Mayer et al, in 1999, showed CO emissions at a level of 180 g/kWh and HC + NO x at a level of 12.6 g/kWh [28]. Mitianiec and Rodak, in 2012, tested a 4.5 kW (two-stroke) engine, showing CO 2 emissions at a similar level of 100 g/kWh.…”
Section: Resultssupporting
confidence: 92%